РОЗРАХУНОК ПАРАМЕТРІВ ІМПУЛЬСНОГО ЕЛЕКТРОДИНАМІЧНОГО ВИПРОМІНЮВАЧА ПРУЖНИХ ХВИЛЬ - Городжа, А.Д.; Городжа, К.А.; Трощинський, Б.О.; Погребний, О.А. (Інститут електродинаміки Національної академії наук України, 2018)
The possibility of using pulsed electrodynamic and induction-dynamic oscillators for the excitation of wave processes in a concrete structure for  diagnosis of its states based on the echo-method is considered. A simplified method for calculating the functional dependence in time of the electromagnetic force when connecting such a converter to a pre-charged capacitor battery is described. The paper takes into account the nonuniform  distribution of current density over the cross section of the  conductors, and also uses the approximation of a relatively small change in the moving part distance during the discharge current flow, which allows us to consider a discharge circuit with constant electrical parameters. The conditions for obtaining the maximum value of the force are determined for a given geometrical dimensions of the oscillator. References 6, figures 3.